Handbook of otolaryngology head and neck surgery - Goldenberg, David; Goldstein, Bradley J. (Thieme, 2018)
Now in full color and packed revised and updated information, this portable book is designed for quick reference. An essential companion for residents, fellows, and beginning clinicians in otolaryngology, and for all physicians and allied professionals in other disciplines who can use rapid and reliable guidance on ENT medicine.